PECULIARITIES OF LABORATORY DIAGNOSTICS OF EXPERIMENTAL BRUCELLOSIS CAUSED BY SAND L-FORMS OF CAUSATIVE AGENT - L. M. Mikhailov; A. I. Kalinovskiy; N. L. Barannikova; M. YU. Shestopalov; N. M. Andreevskaya; V. A. Mikhailova; V. I. Kuznetsov; A. G. Atlas; S. V. Balakhonov (Acta Biomedica Scientifica, 2012)
Comparative evaluation, of bacteriological, serological and PCR diagnostic methods was resulted, at experimental brucellosis in guinea pigs infected, with. S- and. L-forms of the causative agent in different periods of the infection. It was shown that Brucella S-forms were isolated, during six months, L-forms - about one month, by a bacteriological method. Positive PCR results were observed about six months after S- and. L-form infection in animals. Positive slide agglutination, of guinea pig blood sera was revealed, till 12 months by a corpuscular diagnosticum with. S- and. L-forms of Brucella. Complex use of bacteriological, PCR and. serological methods for laboratory diagnostics of atypical brucellosis caused, by Brucella L-form allows to obtain more reliable information, about epizootological-epidemiological situation in non-manifested (non-clinical) infection foci.